Teachers' Role in Character Building through the Pancasila Student Profile Project at MAN 2 Mataram - Salsabila, Ghina; Mustari, Mohammad; Alqadri, Bagdawansyah; Sawaludin, Sawaludin (Jurnal Penelitian Medan Agama, 2025)
The Pancasila Student Profile Strengthening Project (P5) is an integral part of the Merdeka Curriculum aimed at developing the character and competencies of every student. This study aims to examine the role of teachers in shaping students' character through the Pancasila Student Profile Strengthening Project at MAN 2 Mataram. The research method employed is a case study with a qualitative approach, involving interviews, observations, and document analysis. The findings indicate that teachers act as facilitators, motivators, and role models in the character development process. Through various project activities based on Pancasila values, students are encouraged to actively participate, fostering attitudes of tolerance, cooperation, and a sense of responsibility. This study also identifies challenges faced by teachers in implementing the projects, such as limited resources and support from the school. In conclusion, the active role of teachers is crucial in shaping students' character, positively impacting the strengthening of the Pancasila student profile. This research contributes to the development of character education strategies in schools.